PENGARUH LEVERAGE, PROFITABILITAS, DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia) - Dewi Astuti Fetiyatul Ulum, 11.05.52.0053; Wahyu Widati, Listyorini (Students Journal of Accounting and Banking, 2015)
This study aimed to get empirical evidence of: (1) Effect of Leverage Against Company Value (2) Effect of Profitability of the Company Value (3) Effect of Corporate Social Responsibility Disclosure on Corporate Value. Collecton data using purposive sampling method. The study population was all manufacturing companies listed in Indonesia Stock Exchange in 2010-2013 amounted to 155 companies. The sampling technique is purposive sampling. The research sample totaled 150 companies. Analysis of data by multiple regression. Results of this study concluded that: (1) Leverage significant positiveÂ  effect on the value of the company to, (2) Profitability significant positive effect on the value of the company, (3) CSR is not effect onfirm value.Keywords: Leverage, Profitability, CSR, Corporate Values